Karakteristik Organoleptik Telur Asin Dengan Penambahan Jahe Merah (Zingiber Officinale Varietas Rubrum) - Ulfah, Triana; Adiputra, Rachmat; Akhdiyat, Tedi; Firman, Asep (Jurnal Teknologi Pangan dan Hasil Pertanian, 2023)
Eggs are livestock products that have a big contribution in overcoming nutritional problems in society. Generally, eggs only last for two weeks if stored at room temperature. Therefore preservation efforts are very important to maintain the quality of the eggs, so that the quality and nutritional value of the eggs remain good and do not change the taste, smell, color and contents. One way is to preserve them by salting and adding red ginger. Red ginger contains antioxidants, antimicrobials and essential oils that can preserve and give a distinctive aroma. The aim of this study was to determine the effect of adding red ginger (Zingiber officinale Rubrum variety) on the characteristics of salted eggs. The study used a completely randomized design (CRD) with 5 treatments, namely P0: 0% red ginger, P1: 20% red ginger, P2: 30% red ginger, P3: 40% red ginger, and P4: 50% red ginger with 5 times test. The results showed that the characteristics of salted eggs with the addition of 30% red ginger got the highest score in the hedonic method organoleptic test.